Assessment of wheelchair basketball training intensity using heart rate in physically disable people - Santos, Adeliana Cristina Siqueira; Rodrigues, Rosilene Andrade Silva; Balogun, Sikiru Olaitan; Zarour, Felipe Amorim; Freitas, Roberto Luis Marques de; Rodrigues, Daniela Alana Andrade Souto; Andrade, Benedito Robson Monteiro de; Cavalcante, Ramirie Nunes; Napoleão, Amanda Colichio Bini; Fett, Waléria Christiane Rezende; Salomão, Alberto Bicudo; Fernandes, Cleonice Terezinha; et al. (Revista Brasileira de Educação Física e Esporte, 2022)
Objective: To verify the intensity of wheelchair basketball (WB) in people with disabilities (PWD) during 8 weeks intervention. Methods: Longitudinal experimental study of 13 male WB in PWD was assessed and HR, mean heart rate (HRMean) were monitored for the calculation of minimum heart rate (HRMin). %THR were based on the HRpeak. These were then analyzed for possible correlation with the type, level and time of injury, as well as the anthropometric values obtained through bio-impedance. Results: After statistical analysis, of the independent variables, the percentage body fat (p < 0.01), intracellular and extracellular water were found to be positively correlated (p < 0.05) with %THR. The dependent variables, functional classification, level and type of lesion and BMI were not significant (p > 0.05) when correlated with HRpeak. Conclusions: The majority of the participants´ % THR was above 60% of the HRpeak thus indicating that the intervention aided in the promotion of cardiovascular health, besides the mentioned benefits of hydration levels and % body fat of each individual. The present study could serve as a scientific base for the physical educationist alike, and the likes, particularly regarding the use of wheelchair basketball in the rehabilitation or physical fitness workout for PWD.